Perbandingan Pembobotan Kriteria dan Seleksi Kriteria pada Pengelompokan Kinerja Karyawan dengan Fuzzy C-Means - Sanjaya, Rian; Nataliani, Yessica (Universitas Atma Jaya Yogyakarta, 2021)
Abstract. Comparison of Weighted Criteria and Selection Criteria for Employee Performance Grouping with Fuzzy C-Means. The development of information technology makes it easier for companies to do many things and affect company operations. One of the objects affecting the company development is employees. Employeesâ€™ performance can be observed from their discipline, honesty, cooperation, and work quality. The purpose of this study is to group the employees based on their performance using fuzzy c-means. There are two kinds of clustering explained in this paper, i.e., clustering with feature weighting and clustering with feature selection. Using the feature weights of 25%, 30%, 25%, and 20% for work discipline, honesty, cooperation, and work quality, respectively, the clustering with feature weighting gives an accuracy rate of 0.8462. While using feature selection, the fuzzy c-means give 1, where the work discipline and honesty are the critical features in clustering. Therefore, we find that honesty is the most essential feature to cluster the employees based on their performance from this research.Keywords: clustering, employees, fuzzy c-means, feature weighting, feature selectionAbstrak. Perkembangan teknologi informasi mempermudah perusahaan dalam melakukan banyak hal dan mempengaruhi operasional perusahaan. Salah satu objek yang mempengaruhi operasional perusahaan adalah kinerja karyawan. Penilaian kinerja karyawan didasarkan pada empat kriteria, yaitu kedisiplinan, kejujuran, kerja sama, dan kualitas kerja, Tujuan penelitian ini untuk melakukan pengelompokan karyawan dengan fuzzy c-means. Pengelompokan yang dilakukan dalam penelitian ini terdiri dari dua macam, yaitu pengelompokan dengan pembobotan kriteria dan pengelompokan dengan seleksi kriteria. Dengan bobot sebesar 25%, 30%, 25%, dan 20% untuk kriteria kedisiplinan, kejujuran, kerja sama, dan kualitas kerja, pengelompokan dengan pembobotan kriteria menghasilkan akurasi sebesar 0.8462. Pengelompokan FCM dengan seleksi kriteria menghasilkan kriteria kedisiplinan dan kejujuran merupakan dua kriteria yang penting dalam pengelompokan karyawan, dengan akurasi sebesar 1. Dari hasil perbandingan dua macam pengelompokan tersebut didapatkan bahwa kejujuran merupakan kriteria terpenting dalam pengelompokan karyawan berdasarkan kinerjanya.Kata Kunci: pengelompokan, karyawan, fuzzy c-means, pembobotan kriteria, seleksi kriteriaÂ